Building an evidence-base for the training of evidence-based treatments in community settings: Use of an expert-informed approach. (August 2015) - Scudder, Ashley T.; Herschell, Amy D.
Abstract: In order to make EBTs available to a large number of children and families, developers and expert therapists have used their experience and expertise to train community-based therapists in EBTs. Understanding current training practices of treatment experts may be one method for establishing best practices for training community-based therapists prior to comprehensive empirical examinations of training practices. A qualitative study was conducted using surveys and phone interviews to identify the specific procedures used by treatment experts to train and implement an evidence-based treatment in community settings. Twenty-three doctoral-level, clinical psychologists were identified to participate because of their expertise in conducting and training Parent–Child Interaction Therapy. Semi-structured qualitative interviews were completed by phone, later transcribed verbatim, and analyzed using thematic coding. The de-identified data were coded by two independent qualitative data researchers and then compared for consistency of interpretation. The themes that emerged following the final coding were used to construct a training protocol to be empirically tested. The goal of this paper is not only to understand the current state of training practices for training therapists in a particular EBT, Parent–Child Interaction Therapy, but also to illustrate the use of expert opinion as the best available evidence in preparation for empirical evaluation. Highlights: Training consists of preparation, in-person training, consultation, and follow up. Training is a mechanism to facilitate trainees' continual movement towards independence with the training model. Most trainers discussed the importance of progressing with training components based on trainee skill level.